2018
DOI: 10.2217/nnm-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

P38 siRNA-Encapsulated PLGA Nanoparticles Alleviate Neuropathic Pain Behavior in Rats By Inhibiting Microglia Activation

Abstract: As p38 in the spinal microglia plays a critical role in neuropathic pain, we expect that p38 siRNA NPs could be a promising tool for the treatment of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…Neuropathic pain models that are associated with persistent LPA signaling and subsequent activation of MAPK cascades might be candidates for such an approach [42]. Indeed, a series of recent reports demonstrated that pharmacological intervention strategies that attenuate MAPK signaling pathways (either directly or indirectly) alleviate hyperalgesia in preclinical animal models of neuropathic pain [58][59][60][61]. In one of our earlier proteome studies, we have shown that LPA affects the abundance of a number of metabolic enzymes involved in glycolysis [20].…”
Section: Discussionmentioning
confidence: 97%
“…Neuropathic pain models that are associated with persistent LPA signaling and subsequent activation of MAPK cascades might be candidates for such an approach [42]. Indeed, a series of recent reports demonstrated that pharmacological intervention strategies that attenuate MAPK signaling pathways (either directly or indirectly) alleviate hyperalgesia in preclinical animal models of neuropathic pain [58][59][60][61]. In one of our earlier proteome studies, we have shown that LPA affects the abundance of a number of metabolic enzymes involved in glycolysis [20].…”
Section: Discussionmentioning
confidence: 97%
“…An MTT assay was performed in order to test the cell viability caused by siRNA-encapsulated PLGA nanoparticles as per the manufacturer's instructions. Detailed procedures can also be found in previous reports [35].…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…RSS373234; Thermo Fisher, USA) or scrambled siRNA (catalog no. 12935400; Thermo Fisher) were prepared using an emulsification/ solvent evaporation method 32 and their physical characteristics were analyzed with the Zetasizer Nano ZS90 (Malvern Instruments, UK). 23 The NP synthesis and characterization are shown in the Figure 1.…”
Section: Poly(lactic-co-glycolic Acid) Nanoparticles Preparationmentioning
confidence: 99%